Teaching-learning in EVS through Integrated Approach in Early Grades Perceptions and Awareness of Teachers - Sharma, Kavita; Devi, Leisangthem Binita (JOURNAL OF INDIAN EDUCATION, 2012)
Environmental Studies (EVS) is aimed at developing the knowledge, attitude, commitments and skills amongst all, especially the future generations, to enable them work towards the solution of current problems and the prevention of new ones. The National Policy on Education (NPE, 1986) and subsequent Curriculum Frameworks brought out by the NCERT, highlighted the need for including environmental concerns at all levels of schooling. According to NCF- 2005, at the primary level, EVS should be a separate curricular area in Classes III-V. However in Classes I and II, the environmental skills and concerns need to be addressed through Language and Mathematics. This paper highlights the importance of integrated learning in EVS, and perceptions and awareness of the teachers teaching Language and Mathematics in Classes I and II.